PERAN INOVASI DAN STRATEGIK MANAJEMEN MENDUKUNG KESIAPAN SDM MEMASUKI DUNIA KERJA DAN USAHA DI ERA GLOBALISASI – REVOLUSI TEKNOLOGI 4.0 - Giovanni Inez Erika Margaretha; Geraldy Samuel Ivan; Roosganda Elizabeth; Rinsan Hutabarat; Annisaa Soeyono; Ratu Erlina G,; Didik Notosudjono; Arief T. Hardiyanto; Hamzah Bustomi; Hendro Sasongko; Hari Muharam; Martinus Tukiran (Universitas Galuh, 2023)
The era of globalization is called the era of technological revolution 4.0, where technology is developing rapidly, all-digital technology is an absolute requirement for human resources to enter the world of work and business. There are still limited levels of education, skills, competence. The weaker motivation of human resources is the impact of rampant downsizing of the workforce, the bankruptcy of large and small companies. This paper aims to comprehensively present the role and influence of innovation and strategic management on the readiness of human resources to enter the world of work and business in the era of globalization – technological revolution 4.0, interpreted using a descriptive qualitative method of reviewing various literature and study results to enrich writing insights. The results of the writing show that the COVID-19 pandemic has had a very large and significant impact on all aspects of human life and almost all government institutions/organizations/companies in the world, in the economic, social, political, etc. fields, will become history that will never be forgotten for all people. who live in the era of the industrial revolution 4.0. The occurrence of various technological changes is required to increase innovation and creativity in managing strategies to deal with it. Technological change does not automatically bring goodness. Digital literacy is different from a digital mindset. In innovation and strategic execution/implementation, monitoring and evaluation of the most important stages and government alignment (regulation, conducive alignment).